Rancang Bangun Aplikasi Simpan Pinjam Pada Koperasi Karyawan PT. Mega Utama Indah - Subiantara, Dany; Sulistiowati, Sulistiowati; Nurcahyawati, Vivine (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Cooperative Employees PT. Mega Utama Indah  is a business entity in the form of savings and credit cooperatives whose members are employees of PT. Mega Utama Indah. The main constraints faced by the Cooperative Employees PT. Main Mega Indah now is the process of savings is still done manually as the process of loan application, loan approval and repayment of the loan installments. All these processes are still done by recording into a book.These constraints resulted members have to wait to find out whether its proposed loan and the company experienced difficulty in obtaining information and reports - reports required by the cooperative, the required savings and loan applications which includes member registration, loan applications, loan approvals and repayment of the loan installments.Based on trials that have been done, the application can generate reports related to the savings and loan in accordance with the needs of cooperatives, for example, statements about the expected revenues loans, loan report approved or rejected, reports about employees who pay the installments of this month and others reports required cooperative.